Estudo da motilidade gástrica em ratas prunhes diabéticas - Matos, Juliana Fernandes de [UNESP] (2015)
This is a qualitative study aiming at understanding the development of communication skills in undergraduate Nursing students and their teachers' action in such teaching-learning process by considering different types of curricular organizations. The theoretical framework used was based on the studies by Braga and Silva in order to understand communication competence in Nursing teaching and learning. Content analysis according to Bardin was used as a methodological framework. The study was performed in two public institutions of higher education located in inner São Paulo state which employ differentiated teaching methodologies: the Undergraduate Nursing Program of Botucatu Medical School, UNESP, located in the city of Botucatu, and the Undergraduate Nursing Program Marília Medical School, FAMEMA, located in the city of Marília. Data were collected from the perspective of professors and students of the 2nd and 4th years of the Nursing Program, based on guiding questions by means of taped interviews and selfadministered questionnaires, respectively. Ethical issues were considered according to Resolution 466/12 by the National Health Care Council (Conselho Nacional de Saúde - CNS) and the National Research Ethics Committee (Comissão Nacional de Ética em Pesquisa - CONEP), thus obtaining approval by the Botucatu Medical School, UNESP, according to CAAE number: 18459013.0.3001.5413 and Process Number 417.358. Next the research project was submitted to evaluation by the Research Ethics Committee of Marília Medical School, FAMEMA, and approved according to Process Number 432.360. The following thematic categories concerning the factors that influence the development of communication skills in undergraduate Nursing students emerged in the results of the study, according to the professors' perspective: the practice promotes the development of communication skills; the students' individual characteristics; the use of active ...